DECISION ANALYSIS OF MSMEs INVESTMENT IN CILACAP REGENCY - Indra Rachmawati; Tri Yuwono; Muhammad Raihan (SEAN Institute, 2022)
The background of this research is as an effort to restore the economy of Cilacap Regency after the Covid-19 pandemic. Apart from having to try to increase the income of MSMEs, they must also continue to learn to keep up with the times so they can compete with others. One of the skills that MSMEs need to master today is financial literacy. This study used a convenience sampling method with a sample of 21 MSMEs in Cilacap Regency. Testing the hypothesis using multiple linear regression analysis in the form of F test (simultaneous test), T test (partial test), and the coefficient of determination. The test results show that the income variable has no effect on investment decisions. Meanwhile, the financial literacy variable influences investment decisions. Simultaneously the income and financial literacy variables have no effect on MSMEs investment decisions in Cilacap Regency